Survival of a Rhino-Orbital-Cerebral Mucormycosis Patient after Localized Combination Liposomal Amphotericin B Medications: A Case Report - Yang Zhou (Case Reports in Ophthalmology, 2024)
Introduction: The aim of this study was to report a case of ROCM related to nasogastric intubation who was survived by liposomal amphotericin B (LAmB) combination therapy in situ without orbital exenteration. Case Presentation: A 44-year-old woman presented with a 1-week history of rapidly enlarging swelling on the right nose, cheek, and lower eyelid after underwent gastrointestinal decompression. The lesions were derived from the nasal area where the nasogastric tube had been placed. Based on the biopsy results and clinical manifestations, ROCM was diagnosed. Immediate combination therapy with intravenous LAmB and micafungin and multisection debridement of the right facial region were applied. Postoperative treatment included cleaning, irrigating, and local dressing of the wound area using LAmB. LAmB was also used daily as binocular eye drops against deep infection on the eyeballs. The patient recovered well 4 months later and remained free of disease after 40 months of follow-up. Conclusion: This case adds to our knowledge on the potential risk of nasogastric intubation for mucormycosis infection. Nasogastric tube may be the source of infection associated with ROCM. This report evaluates the beneficial effect of LAmB combination therapy in situ for cleaning, irrigating, local wound dressing, and eye drops on lesion areas. The combination of LAmB as cleaning, irrigating, local dressing solution, and eye drops to control intraocular and intraorbital ROCM infection has not been previously reported to our knowledge. These methods provide multiple choices to substitute for orbital exenteration on the survival of ROCM patients.